2021
DOI: 10.1038/s41591-021-01499-z
|View full text |Cite|
|
Sign up to set email alerts
|

Early treatment of COVID-19 with anakinra guided by soluble urokinase plasminogen receptor plasma levels: a double-blind, randomized controlled phase 3 trial

Abstract: Early increase of soluble urokinase plasminogen activator receptor (suPAR) serum levels is indicative of increased risk of progression of coronavirus disease 2019 (COVID-19) to respiratory failure. The SAVE-MORE double-blind, randomized controlled trial evaluated the efficacy and safety of anakinra, an IL-1α/β inhibitor, in 594 patients with COVID-19 at risk of progressing to respiratory failure as identified by plasma suPAR ≥6 ng ml−1, 85.9% (n = 510) of whom were receiving dexamethasone. At day 28, the adjus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
330
3
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 427 publications
(385 citation statements)
references
References 26 publications
3
330
3
13
Order By: Relevance
“…In this issue of Nature Medicine, Kyriazopoulou et al report their evaluation of blockade of the cytokine IL-1 via the recombinant human IL-1 receptor antagonist anakinra in patients with COVID-19 6 . Almost 600 patients with COVID-19 pneumonia who were at risk for respiratory failure, as defined by an elevated serum level of soluble urokinase-type plasminogen activator receptor (suPAR), were randomly assigned to receive either anakinra or placebo (along with standard of care) early during hospitalization, before they needed mechanical ventilation.…”
mentioning
confidence: 99%
“…In this issue of Nature Medicine, Kyriazopoulou et al report their evaluation of blockade of the cytokine IL-1 via the recombinant human IL-1 receptor antagonist anakinra in patients with COVID-19 6 . Almost 600 patients with COVID-19 pneumonia who were at risk for respiratory failure, as defined by an elevated serum level of soluble urokinase-type plasminogen activator receptor (suPAR), were randomly assigned to receive either anakinra or placebo (along with standard of care) early during hospitalization, before they needed mechanical ventilation.…”
mentioning
confidence: 99%
“…Most studies were non-randomized observational studies designed to compare the standard of care treatment plus anakinra versus the standard of care treatment alone [20,[22][23][24]. One study was randomized but not placebo controlled [21] and only one study was a placebo controlled double-blind trial [25]. Interestingly, in one observational study both early and late anakinra administration were investigated [24].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, after a website search, the first placebo-controlled randomized trial on the effect of anakinra in hospitalized COVID-19 patients was identified, at a preprint version at the time of the search [25].…”
Section: Literature Search and Inclusion Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations